Diagnosis and treatment of patients diagnosed with vertebrobasilar insufficiency - V. A. Parfyonov (Медицинский совет, 2014)
The article tells about current approaches to diagnosis and treatment of the most common causes of vertigo: vertebrobasilar insufficiency, benign paroxysmal positional vertigo, phobic postural vertigo.